Digital audio. Interface for non-linear PCM encoded audio bitstreams applying IEC 60958. Non-linear PCM bitstreams according to the MPEG-2 AAC and MPEG-4 AAC formats Part 6, (30th June 2014) - British Standards Institution,
No abstract available